Double aortic arch in a dog (Canis familiaris): a case report - Ricardo, C.; Augusto, A.; Canavese, S.; Marcos, A.; Ticona, E.; Fernandes, M.; Rita, M.; Singareti, F. (Blackwell Verlag Gmbh, 2001)
We herein report a case of a double aortic arch in a 10-week-old male dog of no defined race, which presented episodes of regurgitation at the time of weaning. This vascular malformation was Characterized by the persistence of two aortic arches, right and left, of varying dimensions. The right aortic arch was observed to be larger. During post mortem examination the vessels of the animal were injected with coloured latex bi-centrifuged CIS 1-4 polisopreno which revealed the patency of the two aortic arches. Concomitantly, dilation of the cranial oesophagus causing constriction was observed, indicating megaesophagus, Apart from the constriction, the oesophagus presented normal morphometric parameters in relation to its dimensions.